Evaluation Causes of Hypertension in Some Cities at East Capital Baghdad by Serum Sodium Level - Enamm S. Abdullah (Journal of Global Pharma Technology, 2019)
The studies discuss how the higher serum sodium by high sodium dietary intake effect on management & control of primary hypertension. By take a random 150 patients labeled as primary hypertension with the same medication sources from ministry of health (MOH) in east capital Baghdad. And we neglect the other patients they have other causes that lead to higher blood pressure by measure the serum sodium and questionnaire. The result show there is a higher percent have uncontrolled HTN even take the medications cause of high sodium daily dietary intake reach to 32% in adhamiah, 58% in Al - Saader city, 44% in Al-zaafaraniah.   Keywords: HTN (hypertension), PHCC (primary health care center), serum sodium level.